Smoke measurements during Gestosa-2002 experimental field fires - Miranda, Ana Isabel (2005)
Currently, there is a growing awareness that smoke produced during forest fires can expose individuals and populations to hazardous concentrations of air pollutants. Aiming to contribute to a better understanding of the air pollution phenomenon associated with forest fires, this paper presents and analyses the atmospheric emissions and air quality concentration measurements performed in the 2002 fire experiments at Gestosa, Central Portugal. Two vehicles were equipped with a meteorological station and air quality analysers that were turned on continuously to acquire concentrations of particulate matter, nitrogen oxides and carbon monoxide. Nitrogen and sulfur dioxides were measured using a grid of fixed passive samplers. Also, firefighters and research-team members used passive samplers during the experiments in order to estimate the human exposure to these pollutants. Measurements of volatile organic compound emissions, using Tedlar bags, were carried out. Results were analysed taking into account not only the concentration values but also the variables involved, such as the combustion phase and the meteorology, and identifying possible relationships between them. Despite the small size of the burning plots when compared to wildfires, the measured levels of pollutants were however considerable, indicating the effect of these experiments on the local air quality and stressing the serious levels of air pollution that can be expected during wildfires.